Development of Prepositional-Nominal Combination of a Noun in Modern Russian: Analytics in Grammatical System of Russian Language - A. V. Pryanikov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the analysis of analytical trends in the grammatical structure of the modern Russian language, manifested both at the morphological level - in the system of parts of speech, and at the syntactic level - in the system of types of sentences and its members. Attention is paid to the role in these processes of case forms and prepositional-nominal combination of the noun. It is shown in the article that when they perform a predicative function, their semantics change, leading in some cases to their convergence with the predicate - a hybrid analytical part of speech, highlighted in Russian by P. A. Lekant; factors contributing to this change are described. Particular attention is paid to the analysis of bisubstantive sentences with a locally characterizing meaning: a circle of connective verbs that are a constructive component of a connective substantive predicate is defined, intermediary and qualifying functions performed by them are considered, their syntagmatic potentials are determined, dictum, modus, and phasic connectives are described, which are one of the important elements of general language categories of rational and emotional. The problem of distinguishing between bisubstantive and incomplete (elliptic) sentences, as well as the related problem of distinguishing between the adverbial and predicative functions of spatial syntaxes, is touched upon. The role of Professor P. A. Lekant and his grammar school is particularly emphasized in the study of analyzed units.